Experimental and numerical analysis on SVPWM based grid connected photovoltaic system. (2021) - Palanisamy, R.; Aravindh, P.; Vijayakumar, K.
Abstract: Space Vector Pulse Width Modulation (SVPWM) for 3-phase nested neutral point clamped multilevel inverter (NNPC-MLI) which is suitable for grid connected (PV) system is implemented. The use of nested NPC topology helps in increasing the level in output voltage of the inverter. The main task of the system is to balance the flying capacitor voltage using SVPWM, since we have two capacitors in each leg. In this proposed system inverter generates four level in the output voltage, with minimized voltage stress in each switch. Balancing of neutral point voltage is done by redundant inverter switching states. The implementation of modulation technique for voltage balance control is elaborated in detail. Total harmonic distortion (THD) factor in the output is decreased by SVPWM algorithm in this NNPC topology as compared to other inverter topologies. The input for the inverter is taken from PV source and the output is given to grid connected system. Reduction of switching losses is the other added benefit for the nested configuration. The proposed structure is verified using MATLAB/SIMULINK and the simulation results were obtained.